7-Chloro-4-[(E)-N′-(4-fluorobenzylidene)hydrazinyl]quinoline monohydrate - Marcus V. N. de Souza (Acta Crystallographica Section E, 2010)
The molecule of the title hydrate, C16H11ClFN3·H2O, is slightly twisted, as indicated by the dihedral angle of 9.55 (10)° formed between the quinoline ring system and the benzene ring. The conformation about the C=N double bond is E, and the amine-H atom is oriented towards the quinoline residue. In the crystal structure, the water molecule accepts an N—H...O and makes two O—H...Nquinoline hydrogen bonds, generating a two-dimensional array in the ab plane, which is further stabilized by C—H...O interactions. The most significant contacts between layers are of the type C—H...F.